Impediments to the Development of Kiswahili in the Education Sector in Uganda - Agume, Innocent; Ogechi, Nathan Oyori; Majariwa, David (Journal of the Institute of Kiswahili Studies, 2025)
This study explores the challenges facing the growth of the Kiswahili language in the Ugandan education system. Despite noticeable efforts by the government, the development of Kiswahili through the education system still faces various obstacles. Data was collected from policymakers, coordinators, and language policy implementers, who were purposively selected. Data was analysed using a qualitative approach. Based on a thematic analysis of data, it was established that the growth and development of the Kiswahili language in Uganda, through the education system is still low. This is due to a lack of political will, the absence of effective strategies for implementing language policy regarding Kiswahili, the non-deployment of available Kiswahili teachers, and the inadequacy of materials and resources for teaching and learning Kiswahili. Similarly, ethnolinguistic rivalries have derailed efforts towards Kiswahili development in the education sector. Suggested practical strategies to address these challenges include: strong political will, adequate supply of Kiswahili teaching materials, as well as recruitment and deployment of more Kiswahili teachers. Additionally, tackling negative attitudes and conducting further research on language perceptions will enhance its acceptance and development. These findings are important for policymakers in guiding the formulation of necessary policies that will impact Kiswahili teaching and usage in Uganda.